Large-scale soil–structure physical model (1g) – assessment of structure damages. Issue 4 (December 2013) - Heib, Marwan Al; Emeriault, Fabrice; Caudron, Matthieu; Nghiem, Luyen; Hor, Boramy
Abstract : The paper presents a new large small-scale physical model (6 m 3 ) for studying the damage to structures owing to underground movements: settlement, subsidence and sinkhole. The aim of the research is to study the soil–structure interaction effect of large vertical displacement owing to underground mines. The soil used in the physical model is Fontainebleau sand. The simple masonry structure was built using different materials: polycarbonate, silicone, wood and sugar. The vertical displacement was applied by an electric jack. The physical model is used to reproduce ground surface displacement profiles and the displacement measurement system is based on digital image correlation. Image processing was carried out to analyse the soil and structure displacements. The model allowed comparing the behaviour of soil and structure under different conditions: greenfield and with structure (different positions). Tension cracks appear when the applied subsidence reaches the structure's bearing capacity. The structure damage (cracks) depends on the structure position and the transfer of soil movement to the structure. These results also highlight the importance of the structure position in the development of cracks and damage to the masonry structure. The physical model presents an excellent tool for understanding the behaviour of real buildings and facilities.